Editorial to topical issue "Business and management" - Viktorija Skvarciany (Open Economics, 2018)
A brief overview on the 10th International Scientific Conference "Business and Management" organised by the Faculty of Business Management of Vilnius Gediminas Technical University (Vilnius, Lithuania) on May 3-4, 2018.
Keywords: 330; Business Management; Business Technologies; Economics Engineering; Financial Engineering